Rethinking the Main​​stream Hierarchical Approach of Non-Governmental Organizations in International Development Practice - Hidayati, Umunnisa; Wicaksa, Arif; Alby, Syahroni (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2025)
This study critically examines the continuing relevance and effectiveness of the hierarchical approach that dominates the governance of non-governmental organizations (NGOs) in international development. Using a qualitative method through a systematic literature review spanning 2000 to 2025, the study analyzes forty key sources from scholarly journals, books, and NGO reports, complemented by a case study of local NGO dynamics following the 2010 Haiti earthquake. The findings reveal four major patterns. First, the hierarchical NGO governance system remains highly centralized at the donor and international levels, where decision-making and resources are concentrated. Second, funding mechanisms reinforce short-term project cycles and dependency among local NGOs. Third, accountability structures remain upward (toward donors rather than communities), which limits the responsiveness of aid programs to local needs. Fourth, evidence from post-disaster Haiti illustrates how hierarchical coordination led to fragmented responses, duplication of efforts, and “projectization,” undermining local ownership and long-term recovery. The study bridges post-development critiques of power asymmetry with Ostrom’s polycentric governance framework. This study offers a novel perspective on how NGO governance could be reconfigured to promote shared decision-making, flexible funding systems, and stronger local participation. The research concludes that transforming hierarchical aid structures into more polycentric and locally adaptive governance models is crucial to achieving equitable and sustainable development outcomes in the contemporary global context.